MANAJEMEN PENDIDIKAN ANAK USIA DINI BERBASIS IQ, SQ DAN EQ (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
The article is a discussion on the brain, which consists of the left and right hemispheres. It focuses on the cross functioning of right and left brains by showing the connection between the two as well as uncovering the functions of the brain elements for the early early childhood learning. It argues that in education, the brains have three different functions, i.e. the rational (IQ), the emotional (EQ), and and the spiritual (SQ). In neurosains, playing can stimulate the rational brain activation (IQ), singing (i.e. musics and arts) can stimulate the emotional brain activation (EQ), and story-telling can stimulate the spiritual brain activation (SQ). In addition, quantum learning, which is a strategy to employ motivation, to grow interests, and to build active learning, is closely connected with the brain performance.Keywords: Brain, Quantum Learning, Early Childhood Learning